Universal behavior of the γ⁎γ→(π0, [eta], [eta]′) transition form factors - Melikhov, Dmitri; Stech, Berthold (Physics letters, 2012)
The photon transition form factors of π, η and η′ are discussed in view of recent measurements. It is shown that the exact axial anomaly sum rule allows a precise comparison of all three form factors at high-Q2 independent of the different structures and distribution amplitudes of the participating pseudoscalar mesons. We conclude: (i) The πγ form factor reported by Belle is in excellent agreement with the nonstrange I=0 component of the η and η′ form factors obtained from the BaBar measurements. (ii) Within errors, the πγ form factor from Belle is compatible with the asymptotic pQCD behavior, similar to the η and η′ form factors from BaBar. Still, the best fits to the data sets of πγ, ηγ, and η′γ form factors favor a universal small logarithmic rise Q2FPγ(Q2)∼log(Q2).
Gesehen am 22.11.2018